A Review Of Application Of GFRP In Shear And Flexure To Strengthen The Reinforced Concrete Beam - Yudhvir Yadav2, Vineet Sharma1, (International Journal of Scientific Research and Management (IJSRM), 2016)
A numbers of research are being conducted for the use of frp in the repair and strengthening of reinforced concrete member. Repair and strengthening of concrete structure using such advanced  material is a great revolutionary in the field of structural engineering. Research are being carried out on reinforced concrete beam of different shapes to check the behavior of fibre reinforced polymer on shear and flexural strength of beam. Many authors have performed certain experiment for different parameter and examined the change in property of beam or member. This paper presents review on the effect of different parameter such as type of FRP sheet, dimension of structure, no. of layers of FRP etc on the behavior of RCC beam in shear and flexure. For this analysis of numbers of research is being done and their results have been used here.